2023
DOI: 10.1029/2022ja031085
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Electromagnetic Ion Cyclotron Rising‐Tone Emissions Based on Deep Learning

Abstract: Electromagnetic ion cyclotron (EMIC) waves with fine rising-tone spectral structures have been observed by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Another factor that should be accounted for in the real magnetosphere is the potential nonlinear effect on the HFEMIC wave growth. Magnetospheric chorus-like risingtone EMIC waves are often observed in the inner magnetosphere (Grison et al, 2013(Grison et al, , 2018Nakamura et al, 2014Nakamura et al, , 2016Pickett et al, 2010;Wang et al, 2023) which are attributed to a nonlinear process involving phase trapping and phase bunching (Omura et al, 2010;Shoji et al, 2017Shoji et al, , 2021Shoji & Omura, 2013). Nonlinear theory predicts a much larger growth rate, and this may explain HFEMIC wave growth despite the narrow source region.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that should be accounted for in the real magnetosphere is the potential nonlinear effect on the HFEMIC wave growth. Magnetospheric chorus-like risingtone EMIC waves are often observed in the inner magnetosphere (Grison et al, 2013(Grison et al, , 2018Nakamura et al, 2014Nakamura et al, , 2016Pickett et al, 2010;Wang et al, 2023) which are attributed to a nonlinear process involving phase trapping and phase bunching (Omura et al, 2010;Shoji et al, 2017Shoji et al, , 2021Shoji & Omura, 2013). Nonlinear theory predicts a much larger growth rate, and this may explain HFEMIC wave growth despite the narrow source region.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several observational studies about EMIC wave chirping (Grison et al., 2013; Mursula, 2007; Mursula et al., 1994; Nakamura et al., 2016; Pickett et al., 2010; Y. Wang et al., 2023), theoretical studies are quite limited. Hybrid simulations have clearly demonstrated that EMIC wave frequency chirping is caused by nonlinear processes (Shoji & Omura, 2013).…”
Section: Introductionmentioning
confidence: 99%